Experimental evaluation of room temperature crystallization and phase evolution of hybrid perovskite materials. Issue 27 (30th June 2017) - Prathapani, Sateesh; Choudhary, Divya; Mallick, Sudhanshu; Bhargava, Parag; Yella, Aswani
Abstract : Conversion of PbI2 into FAPbI3 . Abstract : To overcome the problems of thermal, moisture and photo-stability of existing methylammonium based perovskites, formamidinium-based compositions are introduced for photovoltaic application. Formamidinium lead iodide (FAPbI3 ) and methylammonium lead bromide (MAPbBr3 ) mixed compositions of hybrid organic–inorganic perovskite type solar cells have shown the highest efficiency of 22.1%. For FAPbI3, two different polymorphs exist at room temperature: one is the hexagonal non-perovskite phase (δ-phase) and the other is the perovskite cubic phase (α-phase). The non-perovskite phase can be detrimental to the solar cell performance. To eradicate the undesired phase, a systematic evaluation of phase formation and crystallization is necessary. Here, we investigated the room temperature crystallization of the perovskite and non-perovskite phases of FAPbI3 by solvent and antisolvent induced crystallization methods using a two-step sequential deposition method. For each phase, the volume fraction is estimated using the X-ray diffraction technique. At room temperature, the δ-phase is found to grow as long one-dimensional nanorods and its volume fraction increases with the dipping time. It is observed that the presence of an antisolvent has a moderate control on the δ-phase growth. Experimentally, with the detailed solvent-induced time dependent crystallization study, we have proved the effective elimination of the δ-phase and the stability of the FA1− x MA x PbI3 perovskite phase.